2015
DOI: 10.1039/c5cc02624e
|View full text |Cite
|
Sign up to set email alerts
|

A label-free fluorescent molecular switch for a DNA hybridization assay utilizing a G-quadruplex-selective auramine O

Abstract: A sensitive and selective assay of DNA is developed by utilizing a signal transduction strategy with the rational redesign of the hairpin structured G-quadruplex molecular switch (G4-MS) assembled using auramine O (AO). By monitoring the changes of the fluorescent signal, we could identify and further quantitatively determine the target DNA in the samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…It has also been reported that Auramine‐O decays when it is bound to cellulose (Simkovitch and Huppert ) and solid clays (Valandro et al ). The enhancement in fluorescence intensity is similar to a reported case for the mixing of Auramine‐O with htDNA and the amyloid fibril protein (Amdursky and Huppert ; Xu et al ). By keeping C A > 0·1 µ g ml −1 , Auramine‐O can provide more than 60% of the maximum fluorescence intensity within 10 s, which is very reasonable considering the time required for a rapid microbe measurement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has also been reported that Auramine‐O decays when it is bound to cellulose (Simkovitch and Huppert ) and solid clays (Valandro et al ). The enhancement in fluorescence intensity is similar to a reported case for the mixing of Auramine‐O with htDNA and the amyloid fibril protein (Amdursky and Huppert ; Xu et al ). By keeping C A > 0·1 µ g ml −1 , Auramine‐O can provide more than 60% of the maximum fluorescence intensity within 10 s, which is very reasonable considering the time required for a rapid microbe measurement.…”
Section: Discussionsupporting
confidence: 87%
“…Auramine‐O is a nonspecific dye that is embedded in the cell membrane and bound to cell proteins or enzymes in cells (Ivanov et al ; Amdursky and Huppert ). Auramine‐O has excitation and emission wavelengths at 427–435 nm and 495–510 nm respectively (Riemersma and Alsbach ; Chen ; Ivanov et al ; Amdursky and Huppert ; Simkovitch and Huppert ; Xu et al ). It has been used in various biological studies as a stain for synthetic polycarboxylic acids (Braud ) and yeast S. cerevisiae (Brennan and Schiestl ).…”
Section: Methodsmentioning
confidence: 99%
“…2c ). Another small-molecule dye, Auramine O (AO), was recently reported to generate strong fluorescence when mixed with DAP-10 30 and notably was used to study mycobacteria-induced neutrophil phagocytosis in human plasma 31 . In our investigations, fluorescence enhancement of AO without DAP-10 was minor in biological media (2 to 10-fold), whereas that with DAP-10 was significant in both FAB (3,800-fold) and biological media (82 to 494-fold, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further enhancement in emission intensity of this red‐shifted band is observed with increasing PSS concentration, reaching saturation at 0.2 μM of PSS with an overall enhancement factor of ∼100. To this end, emission enhancement for AuO has been reported in various media like viscous solvents, confined environments, and recently, in the presence of some essential bioanalytes, such as, Insulin amyloid fibrils, G‐quadraplexes, etc [55–57] . The fluorescence enhancement of AuO in the presence of these analytes has been assigned to the suppression of intermolecular torsional relaxation in its excited state, compared to a feeble emission yield attained for AuO in its free state in low viscous solvents or in aqueous solutions [58,59] .…”
Section: Resultsmentioning
confidence: 99%